Урботехногенне середовище як інтегральний чинник пристосування рослин - Коршиков, І.І.; Гнатів, П.С. (Промышленная ботаника, 2003)
On an example of the biggest city of Western Ukraine – L’viv – the general tendencies of changes in the condition of an environment due to urbotechnogenesis are analysed. Characteristic shifts of some parameters of the main environment forming factors of the transformed ecosystems are described. The increased complex character of urbotechnogenic environment pressure on vegetation cover is shown and urgent problems of research on mechanisms of woody plants adaptation to the new conditions are formulated.